PHYSICOCHEMICAL PROPERTIES OF BABY INSTANT PORRIDGE FORTIFIED WITH IRON - Herry Santosa; Kristinah Haryani; Noer Abyor Handayani (Chemical Engineering Diponegoro University, 2016)
Fortification is one of solution to alleviate the deficiency of iron. Prevalence of iron deficiency anemia mostly on children under five years, i.e baby instant porridges. Purple sweet potatoes have a potential to be baby instant porridge. The aims of this research was to investigate the effect of fortificant’s type on Fe level as nutritional value, physicochemical properties (bulk density, rehydration capacity, and color) of baby instant porridges made from purple sweet potatoes. This study consists of several stages, which are the stage of making flour, fortification stage, the stage of making instant porridge and phase analysis results. The results show that iron-fortified added to instant baby porridge for nutritional characterization is below to the concentration of additional fortificant. The higher Fe identified on the addition of the iron concentration of 90 ppm (76.12 ppm) and lowest for the addition of concentration of 70 ppm (32.14 ppm). The results of physical properties for bulk density of instant porridge are (0.804 to 0.874 g / ml) showed there is no significant difference between variables and iron fortification no significant effect. Rehydration capacity (1.4 to 1.8 ml/g) with the addition of the iron various variable does not provide significant value changes and provide a lower value than the baby porridge with no fortificant (2 ml / g).